If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = 74 + -4x Reorder the terms: -3 + 7x = 74 + -4x Solving -3 + 7x = 74 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -3 + 7x + 4x = 74 + -4x + 4x Combine like terms: 7x + 4x = 11x -3 + 11x = 74 + -4x + 4x Combine like terms: -4x + 4x = 0 -3 + 11x = 74 + 0 -3 + 11x = 74 Add '3' to each side of the equation. -3 + 3 + 11x = 74 + 3 Combine like terms: -3 + 3 = 0 0 + 11x = 74 + 3 11x = 74 + 3 Combine like terms: 74 + 3 = 77 11x = 77 Divide each side by '11'. x = 7 Simplifying x = 7
| (x-1)(x-1)=(x+3)(x-4) | | 6x^2+9=-4x | | 11/3x+1/6-8/3x+9/16 | | 10-3=7 | | 16-11=5 | | 4x-6/3=6 | | 32=0.5(x+42) | | 4=10x-3x^2 | | 4/11x-9+2/11x=18-3/11x | | 1/2((100-y)-y)=40 | | 1/2(100-2x)=40 | | -3x^2+21x-18=0 | | .15x+.05(12-x)=.10(4) | | 11=((8x+7)/3) | | 0.5(x-(180-x))=50 | | 9n+56=7n-2n-4 | | 3x-4y=4+4 | | ((x+7)/14)=1-(3/2)x | | ((6n-5p)/11t)=c | | -7-9y=63 | | -7(7)+9y=-63 | | 184=.56x | | 74=.56x | | 1/5-1/12 | | y=-3/5(1)-6 | | 54=3y+9 | | 18-7y=108 | | y=3/5-6 | | 4x^2+3=-12x | | 2x-5(-10)=-10 | | 4n-7=33 | | x+5y=47 |